Assessment of intrinsic capacity in the Brazilian older population and the psychometric properties of the WHO/ICOPE screening tool: a multicenter cohort study protocol - Eduardo Ferriolli; Roberto Alves Lourenço; Vitor Pelegrim de Oliveira; Renato Gorga Bandeira de Mello; Renata Eloah de Lucena Ferretti-Rebustini; Leani Souza Máximo Pereira; Alexandre Leopold Busse; Álvaro Campos Cavalcanti Maciel; Amanda Aparecida Oliveira Leopoldino; Ana Cristina Rodrigues Lacerda; Anderson Marliere Navarro; Andre Fattori; et al. (Brazilian Society of Geriatrics and Gerontology, 2024)
Introduction: The World Health Organization (WHO) has proposed to monitor intrinsic capacity (IC) in the older population as a public health strategy through the Integrated Care for Older People (ICOPE) program. Although the program has been developed based on solid concepts, scientific evidence on its practical applicability is still scarce. Objectives: To evaluate IC in Brazilian older adults, its progress over time, and its association with sociodemographic and health factors and outcomes. To evaluate the psychometric properties of the WHO/ICOPE screening tool. Methods: This is a prospective multicenter cohort study with a 36-month follow-up. We will recruit 3838 people aged ≥ 60 years, registered in the health care units included in the study by the participating centers. We will collect sociodemographic and health data and will administer tools to assess IC domains, both those provided for in the ICOPE screening tool and the sequence of confirmatory assessments provided for in the program. Participants will be reassessed every 6 months for 36 months. Expected results: To establish the profile of IC in the study population and to understand its progress and the variables associated with the clinical outcomes of interest. To reveal the diagnostic and psychometric properties of the WHO/ICOPE screening tool. The project is funded by the Brazilian National Council for Scientific and Technological Development (CNPq). Relevance: Understanding the potential use of the ICOPE public health strategy proposed by the WHO within the scope of the Brazilian Unified Health System (SUS) by integrating several research centers in the field of Geriatrics and Gerontology throughout Brazil.